Effects of Abscisic Acid Metabolites and Analogs on Freezing Tolerance and Gene Expression in Bromegrass (Bromus inermis Leyss) Cell Cultures. - Robertson, A. J. (1994)
Optical isomers and racemic mixtures of abscisic acid (ABA) and the ABA metabolites abscisyl alcohol (ABA alc), abscisyl aldehyde (ABA ald), phaseic acid (PA), and 7[prime]hydroxyABA (7[prime]OHABA) were studied to determine their effects on freezing tolerance and gene expression in bromegrass (Bromus inermis Leyss) cell-suspension cultures. A dihydroABA analog (DHABA) series that cannot be converted to PA was also investigated. Racemic ABA, (+)-ABA, ([plus or minus])-DHABA, and (+)-DHABA were the most active in inducing freezing tolerance, (-)-ABA, ([plus or minus])-7[prime]OHBA, (-)-DHABA, ([plus or minus])-ABA ald, and ([plus or minus])-ABA alc had a moderate effect, and PA was inactive. If the relative cellular water content decreased below 82%, dehydrin gene expression increased. Except for (-)-ABA, increased expression of dehydrin genes and increased accumulation of responsive to ABA (RAB) proteins were linked to increased levels of frost tolerance. PA had no effect on the induction of RAB proteins; however, ([plus or minus])- and (+)-DHABA were both active, which suggests that PA is not involved in freezing tolerance. Both (+)-ABA and (-)-ABA induced dehydrin genes and the accumulation of RAB proteins to similar levels, but (-)-ABA was less effective than (+)-ABA at increasing freezing tolerance. The (-)-DHABA analog was inactive, implying that the ring double bond is necessary in the (-) isomers for activating an ABA response.